ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH PEMBOIKOTAN PRODUK PRO ISRAEL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sapta Anugrah; I Wayan Sujana (Jurnal Multidisipliner Kapalamada, 2025)
This study examines changes in corporate profitability before and after the 2023 consumer boycott targeting brands perceived as supporting Israel. Using secondary data from audited financial statements of companies listed on the Indonesia Stock Exchange, the analysis covers five firms—PT Mitra Adiperkasa Tbk, PT Sarimelati Kencana Tbk, PT Fast Food Indonesia Tbk, PT Unilever Indonesia Tbk, and PT MAP Boga Adiperkasa Tbk—over the 2019–2024 period. Profitability is measured using Net Profit Margin, Return on Assets, and Return on Equity. The results show that profitability fluctuated in the pre-boycott period, largely due to the Covid-19 pandemic, which disrupted operations and consumer demand. In the post-boycott period, several firms experienced renewed pressure on profitability, indicated by declining margins and reduced asset efficiency. However, the extent and direction of these changes vary across firms, reflecting differences in exposure to consumer activism, reputational pressure, and firm-level resilience. Overall, the findings suggest that consumer boycotts may be reflected in corporate financial performance, although their impact depends on firm-specific characteristics and industry context.